2012
DOI: 10.1002/jat.2761
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of extremely low‐frequency magnetic fields: reconsidering the melatonin hypothesis in the light of current data on magnetoreception

Abstract: The so-called 'Melatonin Hypothesis' proposed that decreased nocturnal production of melatonin (MLT) might explain the increased risk of breast cancer that has been formerly attributed to extremely low-frequency (ELF) magnetic fields (MF) of weak intensity. Although the risk of ELF MF upon breast cancer was later dismissed, repeated reports were published of partial inhibition of MLT secretion in rats under long-term (≥ 4 weeks) exposure to weak ELF MF. Since 2004, however, this topic has not been experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 107 publications
3
15
0
1
Order By: Relevance
“…) and rat (Fig. ) studies, as others have reported [e.g., Selmaoui and Touitou, ; Kurokawa et al, ; Savitz, ; Jahandideh et al, ; Vanderstraeten et al, ]; human and rat studies are entirely consistent with one another, but only after matching the MF strengths to similar ranges, i.e., B ≲ 50 μT; there seems to be no dose‐dependence between any change in the MLT levels with MF strengths ranging from 0.5 to 100μT as others have reported [e.g., Kato et al, ; Reiter, ; Pfluger and Minder, ; Halgamuge, ]; and the impact of MF on the MLT levels does, however, depend on the ELF‐MF strength, in the regime where ELF‐MFs are weaker than Bthr30normal normalμnormalT (Fig. ).…”
Section: Discussionsupporting
confidence: 78%
“…) and rat (Fig. ) studies, as others have reported [e.g., Selmaoui and Touitou, ; Kurokawa et al, ; Savitz, ; Jahandideh et al, ; Vanderstraeten et al, ]; human and rat studies are entirely consistent with one another, but only after matching the MF strengths to similar ranges, i.e., B ≲ 50 μT; there seems to be no dose‐dependence between any change in the MLT levels with MF strengths ranging from 0.5 to 100μT as others have reported [e.g., Kato et al, ; Reiter, ; Pfluger and Minder, ; Halgamuge, ]; and the impact of MF on the MLT levels does, however, depend on the ELF‐MF strength, in the regime where ELF‐MFs are weaker than Bthr30normal normalμnormalT (Fig. ).…”
Section: Discussionsupporting
confidence: 78%
“…Despite the lack of sufficient empirical data resources, several interesting hypotheses were proposed in the literature, according to which electromagnetic fields affect the pineal gland and its hormone melatonin, interfering with its physiological mechanisms leading to sleep disorders, lower mood, reduced concentration, depression, and the development of certain cancers [115119]. These hypotheses, unsupported by sufficient scientific evidence reflect explicitly the importance of the pineal gland in investigations of related mechanisms of the harmful effects of electromagnetic fields and/or electromagnetic radiation published in journals, textbooks, and even on the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, in light of the present literature, the melatonin hypothesis stating that disruption of melatonin secretion is a main factor in the carcinogenic effects of magnetic fields is not supported by either epidemiological or experimental data (Lewczuk et al, 2014), and thus should be regarded as negatively corroborated and rebutted (Vanderstraeten et al, 2012). Furthermore, the core of the original hypothesis was conceived on the potential association between ELF-MF and breast cancer (Stevens, 1987), which has also been dismissed (Feychting, 2013).…”
Section: Mechanism 1131 the Melatonin Hypothesismentioning
confidence: 93%
“…The majority of in vivo studies have provided very little evidence to suggest ELF-MF reduces melatonin synthesis. However, whilst covering a variety of exposure parameters, these have predominantly occurred in short-term studies (< 2 weeks of exposure duration) conducted on rodents (Vanderstraeten et al, 2012). The issue with this is therefore two-fold as the majority of studies have been conducted on a nocturnally active species whose anatomical location of the pineal gland is largely different from that of humans (Touitou et al, 2006).…”
Section: Mechanism 1131 the Melatonin Hypothesismentioning
confidence: 99%